Direct, indirect, and moderated paths linking work schedules to psychological distress among fly-in, fly-out workers - Parkes, K.R.; Fruhen, Laura; Parker, Sharon (TAYLOR & FRANCIS LTD, 2023)
Fly-in, fly-out (FIFO) workers are exposed to demanding work schedules (including extended rosters, long shifts, and night work) which may contribute to the high levels of psychological distress they report. However, existing evidence is inconsistent. To address these issues, we developed a model of FIFO work schedules and formulated three hypotheses linking objective schedule attributes to psychological distress through direct and indirect paths. We tested these hypotheses in survey data from FIFO workers (N = 2595). Objective schedule attributes (work/leave ratio, cycle duration, hours per shift, and night work) jointly accounted for significant variance in psychological distress; work/leave ratio and hours per shift contributed unique variance. Tests of indirect paths from schedule attributes to psychological distress through two subjective measures (roster satisfaction and lifestyle adaptation) showed that one or both of these paths was significant for each attribute. Moreover, parental status acted as a moderator; having children (relative to no children) interacted with work/leave ratio to predict poorer lifestyle adaptation, and hence higher distress. These findings offer new insights into the complex paths linking FIFO work schedules and psychological distress. The discussion highlights the need for interventions focusing on the design of roster/shift patterns to improve the mental health of FIFO workers.